1996
DOI: 10.1063/1.471456
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the ν1 OH(OD) stretch of HOI and DOI by Fourier transform infrared emission spectroscopy

Abstract: The spectra of vibrationally hot HOI formed in the reaction of alkyl iodides with oxygen atoms are observed by Fourier transform infrared emission spectroscopy. The v=1–3 levels of the OH stretch are observed via the Δv=−1 and Δv=−2 sequence bands. The spectrum of DOI is observed by using 2,2,2-d3-iodoethane as the precursor in the oxygen atom reaction. The v=1–4 levels of the OD stretch are observed in the Δv=−1 sequence band, and the v=1–5 levels of the OD stretch are observed in Δv=−2. Medium resolution spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
6
37
0
Order By: Relevance
“…As i−C 3 H 7 I and (by analogy) n−C 3 H 7 I react rapidly with O( 3 P) (Gilles et al, 1996), it is necessary to assess the potential impact of this on the reported rate constants. The products of the reaction of O( 3 P) with the iodo-propanes are IO, HOI, C 3 H 6 , and C 3 H 7 (Klaasen et al, 1996). By analogy with the reaction of O( 3 P + C 2 H 5 I (Monks et al, 1995) reaction (14a) is expected to dominate with a branching ratio close to 0.9.…”
Section: Ohmentioning
confidence: 99%
“…As i−C 3 H 7 I and (by analogy) n−C 3 H 7 I react rapidly with O( 3 P) (Gilles et al, 1996), it is necessary to assess the potential impact of this on the reported rate constants. The products of the reaction of O( 3 P) with the iodo-propanes are IO, HOI, C 3 H 6 , and C 3 H 7 (Klaasen et al, 1996). By analogy with the reaction of O( 3 P + C 2 H 5 I (Monks et al, 1995) reaction (14a) is expected to dominate with a branching ratio close to 0.9.…”
Section: Ohmentioning
confidence: 99%
“…As can be seen from Table 2, there is good agreement with the observed frequencies of the reactants and products. 5,29 Single-point high-level calculations were then carried out at the stationary points to characterize their energy, and these data are listed in Table 3. These are frozen-core, all-electron calculations without effective core potentials.…”
Section: Computational Approachmentioning
confidence: 99%
“…Finally, the kinetic measurements are combined with ab initio information about the potential energy surface to obtain the thermochemistry of a dominant product, hypoiodous acid. HOI is a major product of the reaction of ground-state atomic oxygen with C 2 H 5 I and larger iodoalkanes 4,5 and recently has been studied by photoionization 6 and FT-IR emission techniques. 7 ∆ f H 298 (HOI) has not previously been determined experimentally, despite its importance in understanding the photodissociation dynamics 8 and photoionization 6 of hypohalous acids and the roles of HOI in the mechanisms of iodine-mediated flame suppression 9 and stratospheric iodine chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…15 Of these works, it is relevant to emphasize the high resolution study of the OH stretch of HOI done by Klaassen et al, 14 which resulted in an estimate of geometrical and vibrational parameters, and the accurate geometry and harmonic force field determination conducted by Ozeki and Saito. 15 In this study, we present a full-dimensional analytical PES obtained from ab initio data calculated using multiconfigurational wavefunctions, with the inclusion of relativistic effects, capable of describing the main features of the [H, O, I] system within chemical accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…tance of a water molecule through CCSD(T)//B3LYP calculations [CCSD(T): coupled-cluster with single double and perturbative triple excitations]; and an extensive investigation of the kinetics of several iodine compounds was conducted by Canneaux et al 10 Experimentally, since the first spectroscopic studies by Ogilvie et al, 11 several investigations on the rovibrational spectra of hypoiodous acid were carried out, [12][13][14] as well as an observation of the pure rotational spectrum of HOI. 15 Of these works, it is relevant to emphasize the high resolution study of the OH stretch of HOI done by Klaassen et al, 14 which resulted in an estimate of geometrical and vibrational parameters, and the accurate geometry and harmonic force field determination conducted by Ozeki and Saito.…”
Section: Introductionmentioning
confidence: 99%